Identification of a Transferrable Terminator Element That Inhibits Small RNA Production and Improves Transgene Expression Levels - de Felippes, Felipe Fenselau; Shand, Kylie; Waterhouse, Peter M. (Frontiers in Plant Science, 2022)
The role of terminators is more commonly associated with the polyadenylation and 3’ end formation of new transcripts. Recent evidence, however, suggests that this regulatory region can have a dramatic impact on gene expression. Nonetheless, little is known about the molecular mechanisms leading to the improvements associated with terminator usage in plants and the different elements in a plant terminator. Here, we identified an element in the Arabidopsis HSP18.2 terminator (tHSP) to be essential for the high level of expression seen for transgenes under the regulation of this terminator. Our molecular analyses suggest that this newly identified sequence acts to improve transcription termination, leading to fewer read-through events and decreased amounts of small RNAs originating from the transgene. Besides protecting against silencing, the tHSP-derived sequence positively impacts splicing efficiency, helping to promote gene expression. Moreover, we show that this sequence can be used to generate chimeric terminators with enhanced efficiency, resulting in stronger transgene expression and significantly expanding the availability of efficient terminators that can be part of good expression systems. Thus, our data makes an important contribution toward a better understanding of plant terminators, with the identification of a new element that has a direct impact on gene expression, and at the same time, creates new possibilities to modulate gene expression via the manipulation of 3’ regulatory regions.